Engineered bimetallic electrode materials for sustainable and selective electroreduction of CO2 into value-added products - Akshay Gandigawad; Hemavathi Manjunath; Chob Singh; Nitin K. Chaudhari; Hanimi Reddy Bapatu; Arvind H. Jadhav (Journal of Environmental Chemical Engineering, 2026)

A modified crop water stress index (mCWSI) for rainfed crops by accounting spatial variability of leaf temperature - Syam Chintala; Shreedevi Moharana; B. V. N. P. Kambhammettu; K. T. Gopika; Lakshmi Lohitha Naidu Ganisetti; Manjunath Kulla (Precision Agriculture, 2026)

Transformative Applications and Innovations in Next-Generation Sequencing Data Analysis - Abhijit Beura; Tikam Chand Dakal; Mangesh Sudhakar Rajguru; Gowrang K. Manjunath; Shweta Mahalingam; Abhishek Kumar (Journal of Applied Genetics, 2026)

Interface-engineered SnS solar cells using an atomic-layer-deposited ZnSnO buffer layer - Jae Yu Cho; Vishesh Manjunath; Yong Tae Kim; Pravin S. Pawar; Rahul K. Yadav; Youngrog Kim; Jin Hyeok Kim; Doh-Kwon Lee; Jaeyeong Heo (Chemical Engineering Journal, 2026)

Digital twin-enabled crop yield prediction in semi-arid agriculture: a continuous feedback machine learning framework - Shrikant Malgi; Manjunath M K; Avinash H T (Theoretical and Applied Climatology, 2026)

Mixed Fruit Cropping in Mango for Higher System Productivity and Profitability - B. L. Manjunath; P. L. Anushma; G. K. Ramesha (Applied Fruit Science, 2026)

Phenotypic characterization of Mangalore melon (Cucumis melo subsp. agrestis var. acidulus) accessions from Southern India based on qualitative and quantitative traits - Ratnakar Manjunath Shet; Raghavendra Gunnaiah; Shantappa Tirkannanavar; Shivanand Hongal; Virupakshi Hiremata; K. C. Venugopal (Genetic Resources and Crop Evolution, 2025)

Boosting the photocatalytic efficiency of g-C3N4 for effective removal of RhB and MB from aqueous medium - Mohamed Masri; Girisha K. B; Abdo Hezam; Khaled Alkanad; Talal F. Qahtan; Qasem A. Drmosh; Faten Masri; Kalappa Prashantha; Manjunath S. H; Sanaa Mohammed Abdu Kaid; Udayabhanu; K. Byrappa (Colloids and Surfaces C: Environmental Aspects, 2025)

Infraspecific hybridisation of muskmelon (Cucumis melo ssp. melo) with mangalore melon (C. melo ssp agrestis var. acidulus) for extended shelf life and improved yield - K. C. Venugopal; Ratnakar Manjunath Shet; Raghavendra Gunnaiah; Rekha B. Chittapur; Virupakshi Hiremata; Shashikanth Evoor; Sarvamangala Cholin; Guranna Prabhuling (Genetic Resources and Crop Evolution, 2025)

Investigative study on hardness and yield strength of Al6061/Sic/Gr. hybrid composite and prediction using machine learning technique - Bharath L; Manjunath T V; Arun Kumar K; Chethan Kumar R; Kiran Kumar S; Prajwal M; Vikas L Lamani (Next Research, 2025)

Butterfly Communities of Bangalore University Campus, Bengaluru, India: Host/Nectar Plant Interactions and Environmental Influences - S. Rajashekara; L. K. Eregowda; G. S. Manjunath; T. K. Manoranjini; R. D. Prathibha; M. G. Venkatesha (Proceedings of the Zoological Society, 2025)

Deciphering salt stress response of pomegranate genotypes (Punicagranatum L.): a comprehensive evaluation - Chandrakant Awachare; Janhavi Pravin Patel; Sebin Sara Solomon; Pinky Raigond; K. Dhinesh Babu; Shilpa Parashuram; Susheel Kumar Sarkar; Mahesh Kumar; C. T. Manjunath Prasad; Rajiv Arvind Marathe; Nripendra Vikram Singh (Plant Physiology Reports, 2025)

Performance evaluation of coffee husk ash based one-part self compacting alkali activated slag concrete mixes - R. Manjunath; J. R. Pushya; K. A. Abhilash Kumar; Kiran K. Shetty (Innovative Infrastructure Solutions, 2025)
Alkali-activated binders are low-carbon alternatives to cement, produced by reacting an alkali activator with an alumino-silicate precursor. However, common alkaline activators like NaOH and Na 2 SiO 3 are highly corrosive, limiting their practical use. This study developed one-part alkali-activated binders from agricultural and industrial waste to address challenges posed by conventional two-part systems. Further performance evaluation of alkali activated slag mixes were evaluated using the developed solid activator. The approach supports sustainable waste management, offers an eco-friendly alternative to Portland cement, and lowers carbon emissions. Using solid alkali-activator sodium metasilicate and precursors like coffee husk ash (CHA), Ground granulated blast furnace slag, and ferrochrome slag, one-part alkali-activated self-compacting concrete (OPASC) mixes were created through Taguchi design experiments. The experimental trials of OPASC were evaluated for fresh, mechanical, microstructural, and durability properties. Results showed flowability between 700 and 765 mm, compressive strength of 50–63 MPa, flexural strength of 3.05–3.58 MPa, splitting tensile strength of 2.7–3.58 MPa, and elastic moduli of 30–32 GPa. These properties were comparable to the reference ordinary Portland cement self-compacting concrete mix, which had a compressive strength of 55 MPa, flexural strength of 4 MPa, splitting tensile strength of 2.8 MPa, and elastic modulus of 30 GPa at 28 days. The OPASC mix showed lower water absorption, high concrete quality (UPV > 4.5), and better performance at elevated temperatures. The study suggests that CHA-based alkali-activated materials can be effectively used, reducing waste and offering viable structural properties.

Polyphenol oxidase (PPO) in wheat (Triticum aestivum): a systematic review on bioactivity, inheritance, functionality and their effects on end products - Rajappa Harisha; Adithya P. Balakrishnan; Karthik Kumar Manjunath; Beera Bhavya; Shaily Singhal; Harshitha Bheemapura Shivakumar; Arvind Kumar Ahlawat; Sanjay K. Singh; Anju Mahendru Singh (Cereal Research Communications, 2025)

Acanthaceae-derived bioactive compounds – Unravelling their therapeutic potential and insights into in silico antiviral applications: A systematic review - Srivatsa Udupa; Manoj Kumar; Nikhil Kumar Ramesha; Sachin Ashok Thorat; Arya Kaniyassery; Harsha K. Chandrashekar; Vivek Pandi; Manjunath B Joshi; Thokur Sreepathy Murali; Annamalai Muthusamy (South African Journal of Botany, 2025)

Unlocking the potential of in-situ thermally reduced graphene oxide anchored with ternary metal oxide-spinel catalyst for sustainable high-performance electrochemical valorisation of CO2 - Sherin Mol C.B; Allwin Sudhakaran; Hemavathi Manjunath; Ashutosh Pandey; Akshaya K. Samal; Mary Nancy T.E; Arvind H. Jadhav (Fuel, 2025)

Piper betle extract inhibits ferroptosis by scavenging oxyradicals, hydroperoxides and inducing NRF2 regulated antioxidants - Veena Ranganathan; Vidyaranyapura S. Deepashree; Jadeppa Gowda; Sumit K. Dey; Souparnika H. Manjunath; Preethi G. Anantharaju; Durgesh Paresh Bidye; Gurubasavaraj V. Pujar; Vinesh J. Maharaj; Rajesh K. Thimmulappa (Food Bioscience, 2025)

Divergent leaf traits of medicinally important Cocculus hirsutus (L.) Diels- morphoanatomical and molecular authentication - Rakshitha H M. Jain; Y.L. Krishnamurty; K. Manjunath; Shashwathi H S (Ecological Genetics and Genomics, 2025)

Development of a novel modified selective medium cefixime–tellurite-phosphate-xylose-rhamnose MacConkey agar for isolation of Escherichia albertii and its evaluation with food samples - Keiji Takehira; Goutham Belagula Manjunath; Noritoshi Hatanaka; Sharda Prasad Awasthi; Bingting Xu; Akira Nagita; Rupak K. Bhadra; Atsushi Hinenoya; Shinji Yamasaki (International Journal of Food Microbiology, 2025)

Structure-based pharmacophore modeling and DFT studies of Indian Ocean-derived red algal compounds as PI3Kα inhibitors - Archana vasuki; H. Jemmy christy; K. Renugadevi; Manjunath Dammalli (Molecular Diversity, 2024)

Segmentation and Volumetric Analysis of Heart from Cardiac CT Images - Rashmitha; K. N. Manjunath; Anjali Kulkarni; Vamshikrishna Kulkarni (Cardiovascular Engineering and Technology, 2024)

Molecular delineation and genetic diversity of Fusarium species complex causing tea dieback in India and their sensitivity to fungicides - Abhay K. Pandey; Manjunath Hubballi; Harshit K. Sharma; R. Ramesh; Somnath Roy; K. Dinesh; Azariah Babu (Crop Protection, 2024)

Assessment of solar-biomass hybrid power system for decarbonizing and sustainable energy transition for academic building - Neelam Baghel; K. Manjunath; Anil Kumar (Process Safety and Environmental Protection, 2024)

Yoga-based lifestyle intervention for healthy ageing in older adults: a two-armed, waitlist randomized controlled trial with multiple primary outcomes - Atmakur Snigdha; Vijaya Majumdar; N. K. Manjunath; Amrutha Jose (GeroScience, 2024)

Effectiveness of hyper and hypothermic application revulsively on range of motion, symptom score and quality of life in patients with cervical spondylosis: a randomized controlled trial - K. J. Sujatha; N. K. Manjunath (Advances in Traditional Medicine, 2024)

A comprehensive review on the effect of turbulence promoters on heat transfer augmentation of solar air heater and the evaluation of thermo-hydraulic performance using metaheuristic optimization algorithms - G. K. Pramod; U. C. Arunachala; N. Madhwesh; M. S. Manjunath (Environment, Development and Sustainability, 2024)
Solar air heaters are characterized by poor thermal performance due to limited heat transfer capability of air, thereby necessitating the need for design modifications. Among a different system performance augmentation technique, turbulence promotors are widely used owing to its effectiveness. Based on design parameters such as geometry, size, pitch and arrangement of turbulence promoters, varying levels of heat transfer increment with the pressure drop penalty is achievable. This led to the development of new designs which could offer on optimum thermo-hydraulic performance for a wide range of Reynolds number. Such research invariably requires a thorough insight of data related to various design parameters and optimal thermal–hydraulic performance range. This article provides a detailed overview of various turbulence promotor designs and their optimal thermal–hydraulic performance ranges compiled from a wide spectrum of experimental and numerical studies. Apart from outlining the general flow characteristics of each turbulator design, this study also evaluates different metaheuristic optimization algorithm such as bonobo optimization (BO), particle swarm optimization and teaching–learning-based optimization algorithm for enhancing the thermal–hydraulic performance parameter (THPP). The study shows that the BO algorithm does not exhibit local trapping due to its self-adapting nature of the optimized parameters which makes it a promising choice for THPP optimization studies in air heater applications. The extensive review also shows that the arrangement pattern of rib turbulator plays a key role in thermo-hydraulic performance augmentation. Based on the BO optimization analysis, the range of THPP is determined for the optimized geometry of turbulence promoters. In the pool of rib design, transverse prism rib, multi-V-rib, multi-V-shaped rib with staggered rib, sinewave-shaped rib with gap and S-shaped ribs exhibits an optimal THPP range of 2.05–3.32, 2.43–2.94, 3.00–3.61, 1.58–3.40 and 2.05–3.74, respectively. Other turbulence promotor designs such as winglet vortex generator, dimple protrusion in arc shape and multi-V-baffles exhibits optimal THPP range of 1.95–2.2, 2.44–3.68 and 1.75–2.01, respectively. At the end, the study proposes key research gaps such as the use of combined ribs and vortex generators and discrete fin arrays of different geometry as future scope of research. Graphical abstract

Ultraviolet and visible light active photothermal copper bismuth oxide nanostructures for solar steam generation - Vishesh Manjunath; Yashwanth K. Reddy; Santosh Bimli; Parvez A. Shaikh; Rupesh S. Devan (Desalination, 2023)

Assessment of morpho-cultural, genetic and pathological diversity of Rhizoctonia solani isolates obtained from different host plants - Asmita Singh; Priya Chandra; Amar Bahadur; Prasenjit Debnath; Gopala Krishnan Subbaiyan; Ranjith K. Ellur; Prashantha Siddappa Tadasanahaller; Akshay Kumar Hosahalli Manjunath; Gaurav Kumar Yadav; Bishnu Maya Bashyal (Journal of Plant Pathology, 2023)

Demystifying image-based machine learning: a practical guide to automated analysis of field imagery using modern machine learning tools - Byron T. Belcher; Eliana H. Bower; Benjamin Burford; Maria Rosa Celis; Ashkaan K. Fahimipour; Isabela L. Guevara; Kakani Katija; Zulekha Khokhar; Anjana Manjunath; Samuel Nelson; Simone Olivetti; Eric Orenstein; et al. (Frontiers in Marine Science, 2023)
Image-based machine learning methods are becoming among the most widely-used forms of data analysis across science, technology, engineering, and industry. These methods are powerful because they can rapidly and automatically extract rich contextual and spatial information from images, a process that has historically required a large amount of human labor. A wide range of recent scientific applications have demonstrated the potential of these methods to change how researchers study the ocean. However, despite their promise, machine learning tools are still under-exploited in many domains including species and environmental monitoring, biodiversity surveys, fisheries abundance and size estimation, rare event and species detection, the study of animal behavior, and citizen science. Our objective in this article is to provide an approachable, end-to-end guide to help researchers apply image-based machine learning methods effectively to their own research problems. Using a case study, we describe how to prepare data, train and deploy models, and overcome common issues that can cause models to underperform. Importantly, we discuss how to diagnose problems that can cause poor model performance on new imagery to build robust tools that can vastly accelerate data acquisition in the marine realm. Code to perform analyses is provided at https://github.com/heinsense2/AIO_CaseStudy .

The Spatiotemporal Patterns of Bus Passengers: Visualisation and Evaluation using Non-negative Tensor Decomposition - Nithin K. Shanthappa; Raviraj H. Mulangi; Harsha M. Manjunath (Journal of Geovisualization and Spatial Analysis, 2023)

Distinct metabolic signatures in blood plasma of bisphenol A–exposed women with polycystic ovarian syndrome - Navya B. Prabhu; Sampara Vasishta; Shashikala K. Bhat; Manjunath B. Joshi; Shama Prasada Kabekkodu; Kapaettu Satyamoorthy; Padmalatha S. Rai (Environmental Science and Pollution Research, 2023)
Polycystic ovarian syndrome (PCOS) is a complicated endocrinopathy with an unclear etiology that afflicts fertility status in women. Although the underlying causes and pathophysiology of PCOS are not completely understood, it is suspected to be driven by environmental factors as well as genetic and epigenetic factors. Bisphenol A (BPA) is a weak estrogenic endocrine disruptor known to cause adverse reproductive outcomes in women. A growing relevance supports the notion that BPA may contribute to PCOS pathogenesis. Due to the indeterminate molecular mechanisms of BPA in PCOS endocrinopathy, we sought liquid chromatography with tandem mass spectrometry (LC–MS/MS), a metabolomics strategy that could generate a metabolic signature based on urinary BPA levels of PCOS and healthy individuals. Towards this, we examined urinary BPA levels in PCOS and healthy women by ELISA and performed univariate and chemometric analysis to distinguish metabolic patterns among high and low BPA in PCOS and healthy females, followed by pathway and biomarker analysis employing MetaboAnalyst 5.0. Our findings indicated aberrant levels of certain steroids, sphingolipids, and others, implying considerable disturbances in steroid hormone biosynthesis, linoleic, linolenic, sphingolipid metabolism, and various other pathways across target groups in comparison to healthy women with low BPA levels. Collectively, our findings provide insight into metabolic signatures of BPA-exposed PCOS women, which can potentially improve management strategies and precision medicine.

Characterization and identification of fungicide insensitive Pestalotiopsis-like species pathogenic to tea crop in India - Abhay K. Pandey; Manjunath Hubbali; Vandana; Pranab Dutta; Azariah Babu (World Journal of Microbiology and Biotechnology, 2023)

Morpho-molecular characterization, diversity analysis and antagonistic activity of Trichoderma isolates against predominant soil born pathogens - N. P. Maheshwary; B. Gangadhara Naik; Amoghavarsha Chittaragi; Manjunath K. Naik; K. M. Satish; M. S. Nandish; T. G. Manu; Balanagouda Patil (Indian Phytopathology, 2022)

Pesticides Exposure-Induced Changes in Brain Metabolome: Implications in the Pathogenesis of Neurodegenerative Disorders - Joel Arvin Rodrigues; Rekha K. Narasimhamurthy; Manjunath B. Joshi; Herman Sunil Dsouza; Kamalesh Dattaram Mumbrekar (Neurotoxicity Research, 2022)
Pesticides have been used in agriculture, public health programs, and pharmaceuticals for many decades. Though pesticides primarily target pests by affecting their nervous system and causing other lethal effects, these chemical entities also exert toxic effects in inadvertently exposed humans through inhalation or ingestion. Mounting pieces of evidence from cellular, animal, and clinical studies indicate that pesticide-exposed models display metabolite alterations of pathways involved in neurodegenerative diseases. Hence, identifying common key metabolites/metabolic pathways between pesticide-induced metabolic reprogramming and neurodegenerative diseases is necessary to understand the etiology of pesticides in the rise of neurodegenerative disorders. The present review provides an overview of specific metabolic pathways, including tryptophan metabolism, glutathione metabolism, dopamine metabolism, energy metabolism, mitochondrial dysfunction, fatty acids, and lipid metabolism that are specifically altered in response to pesticides. Furthermore, we discuss how these metabolite alterations are linked to the pathogenesis of neurodegenerative diseases and to identify novel biomarkers for targeted therapeutic approaches.

Comparative performance of semi-empirical based remote sensing and crop simulation model for cotton yield prediction - N. R. Prasad; N. R. Patel; Abhishek Danodia; K. R. Manjunath (Modeling Earth Systems and Environment, 2022)

Applications of Advanced Geospatial Technology for Expansion of Area under Horticultural Crops in North Eastern Region of India - B. K. Handique; C. Goswami; P. Jena; F. Dutta; R. Samiam; I. Nongrum; D. Jha; P. L. N. Raju; C. R. Deka; R. Sarma; K. Sarmah; H. K. Dutta; et al. (Journal of the Indian Society of Remote Sensing, 2022)

Molecular characterization of phytoplasma strains associated with brinjal little leaf and screening of cultivated and wild relatives of eggplant cultivars for disease resistance - V. Venkataravanappa; M.H. Kodandaram; M. Manjunath; Neha S. Chauhan; K. Nagendran; Shailesh K. Tiwari; B. Sarkar; Govind Pratap Rao (European Journal of Plant Pathology, 2022)

Design of 2-Nitroimidazooxazine Derivatives as Deazaflavin-Dependent Nitroreductase (Ddn) Activators as Anti-Mycobacterial Agents Based on 3D QSAR, HQSAR, and Docking Study with In Silico Prediction of Activity and Toxicity - Nirzari Gupta; Vivek K. Vyas; Bhumika D. Patel; Manjunath Ghate (Interdisciplinary Sciences: Computational Life Sciences, 2019)

Analyses of 3' half genome of citrus tristeza virus reveal existence of distinct virus genotypes in citrus growing regions of India - Kajal K. Biswas; Supratik Palchoudhury; Susheel K. Sharma; Bikram Saha; Shruti Godara; Dilip K. Ghosh; Manjunath L. Keremane (VirusDisease, 2018)

Quantitative Analysis of Phyllanthus Species for Bioactive Molecules Using High-Pressure Liquid Chromatography and Liquid Chromatography–Mass Spectrometry - A. Muthusamy; E. R. Sanjay; H. N. Nagendra Prasad; M. Radhakrishna Rao; B. Manjunath Joshi; S. Padmalatha Rai; K. Satyamoorthy (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

On-site detection of Citrus tristeza virus (CTV) by lateral flow immunoassay using polyclonal antisera derived from virions produced by a recombinant CTV - Yogita Maheshwari; Vijayanandraj Selvaraj; Subhas Hajeri; Chandrika Ramadugu; Manjunath L. Keremane; Raymond K. Yokomi (Phytoparasitica, 2017)

Generation of new leads as HIV-1 integrase inhibitors: 3D QSAR, docking and molecular dynamics simulation - Vivek K. Vyas; Shreya Shah; Manjunath Ghate (Medicinal Chemistry Research, 2017)

Synthesis and antimicrobial evaluation of novel 4-amino-6-(1,3,4-oxadiazolo/1,3,4-thiadiazolo)-pyrimidine derivatives - Poornima Shetty; B. M. Praveen; M. Raghavendra; K. Manjunath; Srinivas Cheruku (Molecular Diversity, 2016)

CoMFA and CoMSIA studies on 6,7-disubstituted-4-phenoxyquinoline derivatives as c-Met kinase inhibitors and anticancer agents - Palak Parikh; Manjunath Ghate; Vivek K. Vyas (Medicinal Chemistry Research, 2015)

Monsoon paddy monitoring and assessment using synthetic aperture radar data under BGREI programme in Odisha, India - Dipanwita Haldar; K. R. Manjunath; Sushma Panigrahy; Varunika Jain; R. S. Gopalan; Mukesh Khullar; Manab Chakraborty; J. S. Parihar (Paddy and Water Environment, 2015)

Host genetic variations in glutathione-S-transferases, superoxide dismutases and catalase genes influence susceptibility to malaria infection in an Indian population - Rayzel C. Fernandes; Marriyah Hasan; Himanshu Gupta; K. Geetha; Padmalatha S. Rai; Manjunath H. Hande; Sydney C. D’Souza; Prabha Adhikari; Angela Brand; Kapaettu Satyamoorthy (Molecular Genetics and Genomics, 2015)

Synthesis of azabicyclo[4.2.0]octa-1,3,5-trien-8-one analogues of 1H-imidazo[4,5-c]quinoline and evaluation of their antimicrobial and anticancer activities - Reshma Kayarmar; G. K. Nagaraja; Manjunath Bhat; Prashantha Naik; K. P. Rajesh; Suchetha Shetty; T. Arulmoli (Medicinal Chemistry Research, 2014)

3D QSAR study of 4H-chromen-1,2,3,4-tetrahydropyrimidine-5-carboxylate derivatives as potential anti-mycobacterial agents - Paresh Patel; Chetan Chintha; Manjunath Ghate; Hardik Bhatt; Vivek K. Vyas (Medicinal Chemistry Research, 2014)

Predictive 3D-QSAR and HQSAR model generation of isocitrate lyase (ICL) inhibitors by various alignment methods combined with docking study - Nirzari Gupta; Vivek K. Vyas; Bhumika Patel; Manjunath Ghate (Medicinal Chemistry Research, 2014)

Homology modeling, binding site identification, and docking study of human β-arrestin: an adaptor protein involved in apoptosis - Chetan Chintha; Nirzari Gupta; Manjunath Ghate; Vivek K. Vyas (Medicinal Chemistry Research, 2014)

Developing Spectral Library of Major Plant Species of Western Himalayas Using Ground Observations - K. R. Manjunath; Amit Kumar; Mehra Meenakshi; R. Renu; S. K. Uniyal; R. D. Singh; P. S. Ahuja; S. S. Ray; Sushma Panigrahy (Journal of the Indian Society of Remote Sensing, 2014)

Design of novel anaplastic lymphoma kinase (ALK) inhibitors based on predictive 3D QSAR models using different alignment strategies - Vivek K. Vyas; Ajay Patel; Nirzari Gupta; Manjunath Ghate (Medicinal Chemistry Research, 2014)

CoMFA and CoMSIA analysis of protein kinase B (PKBβ) inhibitors using various alignment methods - Vivek K. Vyas; Nirzari Gupta; Manjunath Ghate (Medicinal Chemistry Research, 2013)

Variability in airborne bacterial and fungal population in the tertiary health care centre - B. E. Rangaswamy; Fernandes Francis; K. K. Prakash; N. S. Manjunath (Aerobiologia, 2013)

Deducing Rice Crop Dynamics and Cultural Types of Bangladesh Using Geospatial Techniques - Revati More; K. R. Manjunath (Journal of the Indian Society of Remote Sensing, 2013)

Study of morpho-physiological, phenological and reproductive behaviour in protogynous lines of Indian mustard [Brassica juncea (L.)] - U. S. Chandrashekar; Malavika Dadlani; K. Vishwanath; S. K. Chakrabarty; C. T. Manjunath Prasad (Euphytica, 2013)

3D QSAR studies on 5-(2-methylbenzimidazol-1-yl)-N-alkylthiophene-2-carboxamide derivatives as P. falciparum dihydroorotate dehydrogenase (PfDHODH) inhibitors - Vivek K. Vyas; Harshang Parikh; Manjunath Ghate (Medicinal Chemistry Research, 2013)

Greenhouse gas emissions from Indian livestock - Abha Chhabra; K. R. Manjunath; Sushma Panigrahy; J. S. Parihar (Climatic Change, 2013)

Discovery of potent anticonvulsant ligands as dual NMDA and AMPA receptors antagonists by molecular modelling studies - Shailesh V. Jain; Kamlendra S. Bhadoriya; Sanjaykumar B. Bari; Nitendra K. Sahu; Manjunath Ghate (Medicinal Chemistry Research, 2012)

2D and 3D QSAR study on amino nicotinic acid and isonicotinic acid derivatives as potential inhibitors of dihydroorotate dehydrogenase (DHODH) - Vivek K. Vyas; Manjunath Ghate (Medicinal Chemistry Research, 2012)

Photosynthetic rate model in response to environmental parameters for Avicennia marina (Forssk.) Veih. in an Indian mangrove forest - Tanumi Kumar; Sushma Panigrahy; K. R. Manjunath; Chandra Prakash Singh (Acta Physiologiae Plantarum, 2012)

Hyperspectral leaf signature as an added dimension for species discrimination: case study of four tropical mangroves - Sushma Panigrahy; Tanumi Kumar; K. R. Manjunath (Wetlands Ecology and Management, 2012)

Discrimination of Spectrally-Close Crops Using Ground-Based Hyperspectral Data - K. R. Manjunath; Shibendu Shankar Ray; Sushma Panigrahy (Journal of the Indian Society of Remote Sensing, 2011)

Methane Emission Pattern of Indian Rice-Ecosystems - K. R. Manjunath; Sushma Panigrahy; T. K. Adhya; V. Beri; K. V. Rao; J. S. Parihar (Journal of the Indian Society of Remote Sensing, 2011)

A Spatial Database of Cropping System and its Characteristics to Aid Climate Change Impact Assessment Studies - Sushma Panigrahy; Shibendu Shankar Ray; K. R. Manjunath; P. S. Pandey; S. K. Sharma; Anil Sood; Manoj Yadav; P. C. Gupta; N. Kundu; Jai Singh Parihar (Journal of the Indian Society of Remote Sensing, 2011)

QSAR modeling of some substituted alkylidenepyridazin-3-one as a non-cAMP-based antiplatelet agent - Vivek K. Vays; Anurekha Jain; Manjunath Ghate; Deepika Maliwal (Medicinal Chemistry Research, 2011)

Tolerance of Bt corn (MON 810) to maize stem borer, Chilo partellus (Lepidoptera: Pyralidae) - Ramkumar; K. C. Ravi; Farah Deeba; J. N. Nandi; K. S. Mohan; T. M. Manjunath (Plant Cell Reports, 2005)

Wheat growth profile: satellite monitoring and crop yield modelling - K. R. Manjunath; M. B. Potdar (Journal of the Indian Society of Remote Sensing, 2004)

Evaluation of RADARSAT ScanSAR synthetic aperture radar data for rice crop inventory and monitoring - S. Panigrahy; M. Chakraborty; K. R. Manjunath; N. Kundu; J. S. Parihar (Journal of the Indian Society of Remote Sensing, 2000)

Development and validation of spectrometeorological yield models of mustard oil seed crop in Rajasthan state - M. B. Potdar; K. R. Manjunath; N. L. Purohit (Journal of the Indian Society of Remote Sensing, 1999)

Genomic structure, cDNA mapping, and chromosomal localization of the mouse homeobox gene, Hex - Bidyut Ghosh; Harris C. Jacobs; Leanne M. Wiedemann; Anthony Brown; Fiona K. Bedford; Manjunath A. Nimmakayalu; David C. Ward; Clifford W. Bogue (Mammalian Genome, 1999)

Evaluation of spectral bands and spatial resolution of LISS II and LISS III sensors on-board IRS satellites for crop identification - K R Manjunath; N Kundu; S Panigrahy (Journal of the Indian Society of Remote Sensing, 1998)

In vivo clearance of Japanese encephalitis virus by adoptively transferred virus specific cytotoxic T lymphocytes - A. Desai; K. Murali-Krishna; B. Ramireddy; V. Ravi; R. Manjunath (Journal of Biosciences, 1997)

Japanese encephalitis virus infection of mouse cell lines: ability to prime mice for generation of virus specific cytotoxic T lymphocytes and differences in CTL recognisable viral determinants - K. Murali-Krishna; V. Ravi; R. Manjunath (Archives of Virology, 1995)

Correlation of histologic types of carcinoma of the uterine cervix and human papillomavirus and herpes simplex virus type 2 DNA sequences in the uterine cervical biopsies - P. Seth; H. Kaur; R. Kaur; K. Verma; N. Manjunath (Archives of Virology, 1988)